Preparation and application of poly(hydroxamic acid)-kenaf fiber chelating ion exchanger for the removal of chromium and nickel from aqueous solutions - Mohamat Yusuff, Soleha (2013)
Research on the removal of heavy metal ions from water and wastewater is a necessary mission of protecting human health and the environment. Adsorption is the promising technique compared to the others due to its low-cost, easy operating and effectiveness characteristic. Besides produced the effective adsorbent, many researchers has great attention to use low-cost and non-petroleum based materials such as natural fibers. Fibrous plant of kenaf (Hibiscus cannabinus L.) is one of the commercial crops in Malaysia which is used in various sectors due to its properties. Therefore the application of kenaf fiber for removal of heavy metals from water and wastewater is worth explored. The fiber was grafted through polymerization with methyl acrylate and the ester group was reacted with hydroxylamine hydrochloride to form poly(hydroxamic acid) which is known able to form complex with metal ions. The effects of important parameters during grafting process which can affect percentage of grafting such as amount of catalyst, co-catalyst and monomer, temperature and time of grafting were studied followed by the effects of pH and amount of hydroxylamine hydrochloride during hydroxyaminolysis which can affect the percentage of metal removal. The characteristics of kenaf fiber, grafted kenaf fiber and functionalized kenaf fiber prepared were characterized by colored complex test with vanadium ion, TGA, CHN/O analysis, BET surface analysis, FTIR and SEM-EDX spectroscopy. This research also investigate the effects of pH, reaction time, initial metal concentrations, adsorbent dosage and temperature on the adsorption capacity for Ni (II), Cr (III) and Cr (VI) ions removal. The optimum amount of catalyst, co-catalyst and monomer for grafting copolymerization of methyl acrylate onto 5.0 g of kenaf fiber were 15 mL, 0.50 g and 30 mL, respectively. The percentage of grafting value was higher with 2 hr of grafting reaction at 45 oC. In preparation of PHA-kenaf, 1.0 g of hydroxylamine hydrochloride in 15 mL of methanolic solution at pH 13 reacted with 1.0 g PMAkenaf gave the high value of adsorption capacity. FTIR spectra, TGA, BET analysis, CHN/O elemental analysis, colored complex test with vanadium ion, SEM images and EDX spectra showed the characteristics of kenaf, PMA-kenaf and PHA-kenaf. The optimum pH for Ni (II), Cr (III) and Cr (VI) adsorptions were 6, 4 and 3, respectively. The adsorption capacities were dependent on Ni (II), Cr (III) and Cr (VI) ions concentrations, reaction time, and adsorbent dosage. The adsorption process of Ni (II), Cr (III) and Cr (VI) followed pseudo second-order model. The equilibrium data followed the Langmuir model with maximum adsorption capacity of Ni (II), Cr (III) and Cr (VI) were 43.29, 13.42 and 30.12 mg/g, respectively. The adsorption processes were endothermic and spontaneous.